Tyrosine biosynthesis, metabolism, and catabolism in plants - Schenck, Craig A.; Maeda, Hiroshi A. (Phytochemistry (Oxford), 2018)
L-Tyrosine (Tyr) is an aromatic amino acid (AAA) required for protein synthesis in all organisms, but synthesized de novo only in plants and microorganisms. In plants, Tyr also serves as a precursor of numerous specialized metabolites that have diverse physiological roles as electron carriers, antioxidants, attractants, and defense compounds. Some of these Tyr-derived plant natural products are also used in human medicine and nutrition (e.g. morphine and vitamin E). While the Tyr biosynthesis and catabolic pathways have been extensively studied in microbes and animals, respectively, those of plants have received much less attention until recently. Accumulating evidence suggest that the Tyr biosynthetic pathways differ between microbes and plants and even within the plant kingdom, likely to support the production of lineage-specific plant specialized metabolites derived from Tyr. The interspecies variations of plant Tyr pathway enzymes can now be used to enhance the production of Tyr and Tyr-derived compounds in plants and other synthetic biology platforms. [Display omitted] •Tyrosine is mainly synthesized in the plastids via the arogenate intermediate in plants.•Alternative cytosolic tyrosine biosynthetic pathways are present in some plant lineages.•Tyrosine serves as a precursor to a myriad of plant natural products.•Feedback insensitive tyrosine biosynthetic enzymes can be used to enhance production of tyrosine-derived natural products.•Regulatory mechanisms of tyrosine homeostasis remain largely unknown.